Familial camptodactyly - Brites, MM (2008)
Camptodactyly is a permanent flexion deformity at the interphalangeal joints, usually at the proximal, interphalangeal joints. It is by far most commonly encountered in the little finger, but it can occur in any of the others, and may be associated with a deformity in the little finger or not. It is usually bilateral. It can also appear in the toes, the second toe being the most frequently affected. This deformity can appear in two different situations: it can occur in isolation, or can be a part of a malformative syndrome. It can also be sporadic or be transmitted as an autosomal dominant trait [1, 5, 7, 8]. We report a case of familial camptodactyly not associated with any other disorders: the differential diagnoses included scleroderma and Dupuytren's contracture.